PENINGKATAN KETERAMPILAN BERPIKIR KRITIS SISWA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN INKUIRI TERBIMBING PADA KONSEP ELASTISITAS DI KELAS XI MAN DARUSSALAM KABUPATEN ACEH BESAR - Nuraini Fatmi (Center for Research and Community Service (LPPM) University of Abulyatama, 2017)
Based on the results of field observations to study physics, discovered the problem that when the learning process is still on going in other words the student center still conventional. The process of teaching and learning by teachers is an activity students store information in a passive mind and considered vacant, students only received verbal information from books and teachers. Though the learning of physics is based on the scientific principles of good processes, products and scientific attitude should be oriented guided inquiry. The research objective was to determine: 1) increase students' critical thinking skills using guided inquiry models, 2) the activity of teachers in the learning process by using a model of guided inquiry, 3) the activity of students in the learning process by using a model of guided inquiry, 4) The response of students to the learning model in teaching and learning classroom XI IPA1 MAN Darussalam academic year 2015/2016 amounted to 24 students. Data were obtained from the tests, observation and questionnaires, the research methods class act. The technique of data analysis using descriptive statistics with percentage formula. Based on the results of this study indicated that: 1) critical thinking skills test results obtained value (56.45) in the first cycle, (63.96) in the second cycle and (72.70) in the third cycle. 2) the activity of the dominant teacher appears that aspects of planning and carrying out simple investigations and communicate the results of the investigation (14.6%). 3) the dominant activity of students appearing is formulate aspects of the problem and communicate the results of the investigation (14.6%). 4) The response of students feel that the inquiry learning model to increase critical thinking skills using guided inquiry learning model achieving the highest percentage of 94.21%.